THE EFFECTIVENESS OF TEACHING VOCABULARY BY USING PICTURE MEDIA TOWARD STUDENTS’ SPEAKING ABILITY AT EIGHTH GRADE STUDENTS OF SMP IT AL ASROR SEKAMPUNG - Yatino Dawamuddin (Prodi Tadris Bahasa Inggris)
The vocabulary is an important part in speaking. If we learn grammar, speaking, listening, without having the problem, the writer must give a good strategy in teaching vocabulary to increase all of them, especially in speaking skill. In Junior high school level, English is introduced as a new subject. Most of the students never learn it before. The writer thinks that vocabulary mastery is the most important, because vocabulary is an essential means in teaching language skill, especially in speaking skill. Students who understand a vocabulary will not be misled in interpreting the meaning of the vocabulary. When they have known the vocabulary, ofcourse they can speak easily. This research is used quantitative reseach. Researcher test hypotheses that are stated at the beginning. The Concepts are in the form of distinct variables. Measures used are systematically created before data collection and are standardized. The data are in the form of numbers from precise measurement. Theory is largely causal and deductive. Procedures are standard, and replication is frequent. Analysis proceeds by using statistics, tables, or charts and discussing how what they show relates to hypotheses. The result of this research is student can easier understanding of learning vocabulary and more interest about the media, the student’s speaking ability also influenced by learning vocabulary.